Implementation of FinFET based 14T SRAM Memory Cell using Modified Lector Technique & Dual Threshold - N. Siva Sankara Reddy, P. Chandra Sekhar, Ramesh Gullapally (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Static Random Access Memory (SRAM) can't become any smaller because to the sorts of materials and leakage testing used in today's large-scale silicon MOSFETs. This study uses a double edge and modified LECTOR method to create new tradeoffs in 14-semiconductor SRAM cells. Because of their outstanding transportation capabilities and the possibility for usage on large-scale processing and production, FinFETs are great replacements replacing outdated CMOS electronics. This test especially investigates a double edge value-based SRAM cell design. There are 14 semiconductor materials used in the design. According to the simulation's findings, FinFET-based circuits are more energy-efficient and reliable than scaled circuits. They are more susceptible to variances and flaws nevertheless. These findings suggest that in terms of power efficiency, FinFETs are far superior to CMOS.